Molecular Characterization and Histopathological Correlation of Antibiotic Resistance Genes in Clinical Isolates of MRSA in Pakistani Hospitals - Irshad, Zubeda; Khan, Azeem Gohar; Imran, Tabbassum; Sadikova, Sabokhat; Kanwal, Sughra; Saboor, Abdus (Journal of Neonatal Surgery, 2025)
Background: Methicillin-resistant Staphylococcus aureus (MRSA) is a major public health concern worldwide due to its multidrug resistance and associated morbidity. In Pakistan, hospital-based prevalence remains high, yet limited data exist on the molecular determinants of resistance and their correlation with tissue pathology. Objective: To characterize antibiotic resistance genes in clinical isolates of MRSA from Pakistani hospitals and to assess their correlation with histopathological features of infection. Methodology: A cross-sectional study was conducted from January to December 2024 in three tertiary-care hospitals. A total of 406 clinical MRSA isolates were included. Standard microbiological procedures and PCR assays were used to detect resistance genes. Histopathological specimens from corresponding infection sites were examined for necrosis, abscess formation, vascular invasion, and chronic inflammation. Data were analyzed using SPSS 25. Associations were tested with Chi-square, t-test, and multivariable logistic regression. Results: All isolates carried mecA, while mecC was present in 3%. Among accessory genes, ermA (31%), ermC (24.1%), tetK (20.9%), tetM (18.2%), and aac(6’)-aph(2’’) (16.5%) were frequent, whereas vanA (2.2%) and vanB (0.7%) were rare. Gene-positive isolates exhibited significantly higher rates of severe necrosis (p < 0.001), abscess formation (p = 0.002), and vascular invasion (p = 0.004). Logistic regression identified ermA (p = 0.001), tetM (, p = 0.041), and prior antibiotic exposure (p = 0.046) as independent predictors of severe histopathological changes. Conclusion: MRSA in Pakistani hospitals demonstrates widespread mecA carriage with frequent accessory resistance genes, which correlate with more severe tissue pathology